2019
DOI: 10.3233/rnn-180894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paired-pulse stimulus parameters on the two phases of short interval intracortical inhibition in the quadriceps muscle group

Abstract: Background: Short interval intracortical inhibition (SICI) is commonly used to assess inhibition in the motor cortex and is known to be affected by the paired-pulse stimulus parameters (i.e., interstimulus interval [ISI], conditioning stimulus intensity [CSI] and test stimulus intensity [TSI]) used during testing. While the effects of stimulus parameters are well-studied in the upperextremity, evidence in the lower-extremity is lacking.Objective: To comprehensively examine the effects of alterations in paired-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…If using these criteria, our results would have demonstrated that SICI averaged across all intensities demonstrated “good” (ICC 3,1 = 0.62–0.73) reliability for VL and VM, and “moderate” reliability for RF (ICC 3,1 = 0.43). Lastly, we used a specific test stimulus intensity (i.e., 140% AMT) and ISI (3 ms) to elicit SICI based on previous single‐ and paired‐pulse TMS research in different muscles of the quadriceps (Doguet et al, 2017; Krishnan, 2019; Latella et al, 2017; Leung et al, 2018). This warrants consideration when comparing and discussing the current results in relation to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If using these criteria, our results would have demonstrated that SICI averaged across all intensities demonstrated “good” (ICC 3,1 = 0.62–0.73) reliability for VL and VM, and “moderate” reliability for RF (ICC 3,1 = 0.43). Lastly, we used a specific test stimulus intensity (i.e., 140% AMT) and ISI (3 ms) to elicit SICI based on previous single‐ and paired‐pulse TMS research in different muscles of the quadriceps (Doguet et al, 2017; Krishnan, 2019; Latella et al, 2017; Leung et al, 2018). This warrants consideration when comparing and discussing the current results in relation to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) is a common technique used to investigate neurophysiological responses in humans, with paired‐pulse TMS paradigms providing insight into intracortical networks (Krishnan, 2019; Matamala et al, 2018). Specifically, short‐interval intracortical inhibition (SICI) is thought to reflect inhibition mediated by gamma‐aminobutyric acid type‐A (GABA A ) receptors (Ziemann, 2003; Ziemann et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate regression analyses were performed using the data from the reconstructed limb, nonreconstructed limb, symmetry values, and the change scores to comprehensively understand the contributions of knee flexion angle and vGRF to peak knee extension moment during gait. We adopted an inclusive statistical approach where both classical and Bayesian regression analyses were performed to measure statistical significance ( P value) and the Bayes factor (BF 10 ), respectively (20)(21)(22)(23)(24)(25). More details regarding the Bayesian analysis and how to interpret the results of this analysis are provided in the JASP manual (http://static.jasp-stats.org/Manuals/Bayesian_Guide_v0_12_2_ 1.pdf).…”
Section: Methodsmentioning
confidence: 99%
“…However, a direct comparison between TMS-induced muscle relaxation rate and the relaxation rate determined from the resting twitch evoked by femoral nerve stimulation has not been reported for the knee extensors (KE). It is possible that TMS-induced muscle relaxation rate behaves differently for KE, when compared with other muscles, due to different somatotopic organization and recruitment thresholds (Leung et al 2018 ; Krishnan 2019 ), functional role (Maffiuletti et al 2008 ) as well as neuromuscular aspects (Brouwer and Ashby 1990 ; Saltin and Gollnick 2011 ; Vernillo et al 2018 ; Temesi et al 2019 ). Therefore, understanding whether TMS is a valid technique that can be used for measuring KE relaxation rate is important because KE is (1) responsible for knee-extensor force production and therefore plays a key role during ambulatory, functional and sport activities (Maffiuletti et al 2008 ); and (2) commonly used in studies investigating muscle fatigue with TMS (e.g., Sidhu et al 2009 ; Goodall et al 2012 ; Klass et al 2012 ; Temesi et al 2013 ; Vernillo et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%